ANALISIS YURIDIS TERHADAP PENYALAHGUNAAN NARKOTIKA JENIS SABU-SABU DAN PIL EKSTASI DITINJAU DARI SEGI HUKUM PIDANA DALAM PUTUSAN NOMOR : 473/PID.SUS/2015/PT.MDN - Sanna Friani Manalu; Arta Rumiris Sipahutar; Sampe Raja Sinaga; Mesias J.P Sagala (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2019)
The study was intended to explore the application of law for drug abusers of the type of methamphetamine based on court decision No. 473 / PID.SUS / 2015 / PT.MDN. Narcotics is an interesting issue to discuss because it is always followed by opinions that are pro and contra. The provision of criminal law can be interpreted as one of the penalties given to someone who violates the applicable law. In this case, a narcotics addict can be considered a violator of the law, because he has been abusing drugs. In accordance with the times, which are marked by technological advances, information and communication can multiply people to engage in criminal acts. The results of this study indicated that the application of material criminal law to decision No. 473 / PID.SUS / 2015 / PT.MDN had to be in accordance with the demands of the public prosecutor. Because in the statement of the defendant disclosed in court, (1) it was mentioned that there was a sale and purchase transaction carried out by the defendant with someone he did not know. (2) Legal considerations against judges who imposed criminal sanctions on the verdict No. 473 / PID.SUS / 2015 / PT.MDN had to be based on the consideration of the public prosecutor and judge, the offender could be sentenced to life imprisonment or at least imprisonment for 5 years or a maximum of 20 years and a fine of at least 1 billion rupiahs or at most 10 billion rupiahs by applying article 114 paragraph (1) of Law No. 35 2009 on narcotics.